“Creating Links”: The Involvement of Service Users and Carers in the Provision of Social Work Education in England - LINKS GROUP, CREATING (Participatory Social Work: Research, Practice, Education, 2019)
This chapter sets out the processes and outcomes of the involvement of a group of service users and carers in the provision of social work education at the School of Health and Social Work University of Hertfordshire, England. The School was one of the first adopters of service user input into the provision of learning and teaching in social work in England. User involvement in social work services is well established in the discourse about social work services in relation to some service user groups in the UK, although its reality and extent in reality is contested, and service users and carers’ meaningful involvement in social work education on a practical level is less frequently discussed. The chapter sets out the model of participation adopted and evolved over the period of existence of the group of service users and carers who chose the name, “Creating Links” for their steering committee.